Combining Recession Probability Forecasts from a Dynamic Probit Indicator - Thomas Theobald (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
This paper analyzes the real-time out-of-sample performance of three kinds of combination schemes. While for each the set of underlying forecasts is slightly modified, all of them are real-time recession probability forecasts generated by a dynamic probit indicator. Among the considered aggregations the most efficient turns out to be one that neglects the correlations between the forecast errors.
urn:nbn:de:101:1-201202285303
Keywords: 330; Konjunkturprognose; Prognoseverfahren; Probit-Modell; Theorie